The Acinetobacter baumannii Oxymoron: Commensal Hospital Dweller Turned Pan-Drug-Resistant Menace - Roca Subirà, Ignasi; Espinal, Paula; Vila-Farrés, Xavier; Vila Estapé, Jordi (Frontiers in Microbiology, 2012)
During the past few decades A. baumannii has evolved from being a commensal dweller of health-care facilities to constitute one of the most annoying pathogens responsible for hospitalary outbreaks and it is currently considered one of the most important nosocomial pathogens. In a prevalence study of infections in intensive care units conducted among 75 countries of the five continents, this microorganism was found to be the fifth most common pathogen. Two main features contribute to the success of A. baumannii: i) A. baumannii exhibits an outstanding ability to accumulate a great variety of resistance mechanisms acquired by different mechanisms, either mutations or acquisition of genetic elements such as plasmids, integrons, transposons or resistant islands, making this microorganism multi- or pan-drug resistant and ii) The ability to survive in the environment during prolonged periods of time which, combined with its innate resistance to desiccation and disinfectants, makes A. baumannii almost impossible to eradicate from the clinical setting. In addition, its ability to produce biofilm greatly contributes to both persistence and resistance. In this review, the pathogenesis of the infections caused by this microorganism as well as the molecular bases of antibacterial resistance and clinical aspects such as treatment and potential future therapeutic strategies are discussed in depth.